Effectiveness of an Educational Program on Nurses’ Knowledge and Attitudes about Pain Assessment and Management in Imam Hussein Medical City in Holy Karbala - Duaa Raad Saied; Khalida Awan Mansour (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Pain is a physical and emotional distressing sensation that is associated with tissue damage,both actual and potential. Inadequate pain management has been shown to affect patient outcomes byprolonging the hospitalization period and delaying the recovery process; therefore, pain management hassignificant implications. A descriptive-analytic (quasi-experimental) design was conducted to determinethe effectiveness of an educational program on nurses’ knowledge and attitudes about pain assessment andmanagement in imam Hussein medical city in holy KarbalaMethodology: A quasi-experimental design was used to guide this study, it was applied by use of the preand post-test approach for two groups of samples (study and control). It was conducted at the Imam Husseinmedical city during the period from 15th November 2020 to 9th March 2021.Results: The study findings show that participants’ age group at a level (20-29 years) were (63.3%) of thestudy group, and (53.3%) of the control group. (50.0%) of the study group were male, while (46.7%) of thecontrol groups were female.Findings showed that the total mean score was unacceptable level for both study and control groups beforegiving intervention, while a good level for the study group post-intervention, regarding the knowledge andattitude of pain assessment and management. Highly statistically significant differences in post-test for thestudy group as compared with the control groups for knowledge and attitude domains.Conclusion: The study indicates that the education program had a positive effect on nurse’s knowledge andattitude about pain assessment and management. This conclusion is based on the result of our study thatreveals significant differences between pre-intervention and post-intervention.Recommendations: The study recommended that educational and training programs be routinely providedto develop their knowledge and attitude, and keep them up to date on pain management, also, the distributionof the applied educational program of this study as a booklet or posters for the hospital staff.